A comparative study between Malaysia and United States on the law of defence of infancy: reducing the age of infants to become liable under the law / Adlin Shuhaili Mazlan, Dona Putri Sakinah Don Putra and Nik Nuraisya Nik Badrul Azahar - Mazlan, Adlin Shuhaili; Don Putra, Dona Putri Sakinah; Nik Badrul Azahar, Nik Nuraisya (2015)
This is a study on The Defence of Infancy in the Child Act 2001. The study concentrates on primarily on the rights of the child in conjunction to the aim of the act at protecting the child's best interest. On the basis that children below the age of ten are already able to understand the nature of their act whether good or bad. This research addresses the issue of the current provision on the law of Infancy Defence in Malaysia and could the age be reduced to enable children to be recognized under the eyes of law. Hence be protected and effectively morally corrected in the further process of the juvenile justice system. The objective of this research would be to examine the law on the defence of infancy under the Childs Act 2001 and the Model Penal Code in United States; and whether the existing law and practice is sufficient to suit with the development of the children's mind in the present era. This research discovers that the law itself may not be the main contributing factor to the issue, but it is in the execution of the system of juvenile justice particularly in the rehabilitation schools. Thus, the recommendations are suggested in hope to be able to improve the current juvenile justice system that may be detrimental to the children.